2011
DOI: 10.3390/rs3030587
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Topography Changes and Elevation Accuracies Using a Mobile Laser Scanner

Abstract: Laser measurements have been used in a fluvial context since 1984, but the change detection possibilities of mobile laser scanning (MLS) for riverine topography have been lacking. This paper demonstrates the capability of MLS in erosion change mapping on a test site located in a 58 km-long tributary of the River Tenojoki (Tana) in the sub-arctic. We used point bars and river banks as example cases, which were measured with the mobile laser scanner ROAMER mounted on a boat and on a cart. Static terrestrial lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 27 publications
(34 reference statements)
2
77
0
2
Order By: Relevance
“…Therefore, in order to cope with these issues, TLS has often been employed in combination with other techniques. A possible solution has been proposed in Vaaja et al [91] and Hackney et al [66], who employed a mobile laser scanning (MLS) system to map changes (erosion/deposition) in riverine topography. In case the MLS sensor is installed on a car, only vehicle-accessible sites are suitable for the application of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to cope with these issues, TLS has often been employed in combination with other techniques. A possible solution has been proposed in Vaaja et al [91] and Hackney et al [66], who employed a mobile laser scanning (MLS) system to map changes (erosion/deposition) in riverine topography. In case the MLS sensor is installed on a car, only vehicle-accessible sites are suitable for the application of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the current state of research in this area has shown that there are a large number of publications dedicated to tasks of construction of digital models of buildings, the detection of the surface of the earth and the reconstruction of the road surface, detection and recognition of road facilities on the basis of MLS data [5,7,8].…”
Section: Methodsmentioning
confidence: 99%
“…Compared to traditional ALS, MLS is better suited to mapping smaller areas with a higher point density . The method can also be used to acquire very precise multi-temporal data for change detection (e.g., Vaaja et al, 2011). The geometry of MLS is dependent on the location of the sensor, and the pulse density varies as a function of the range.…”
Section: Introductionmentioning
confidence: 99%